Prevalence of Vitamin A Deficiency in School Going Children - E. Arjun; Cheeti Srinivas Kalyan Rao; T. Ananth (Asian Journal of Clinical Pediatrics and Neonatology, 2017)
Background: Vitamin A Deficiency is prevalent in India and has been stated to be the most preventable cause of blindness. Aims and Objectives: The aim of this study was to determine the prevalence of Vitamin A Deficiency in the school going children of our geographic sector. Methods: The present cross-sectional study involved 250 school going children aged 5-15 years. Necessary demographic data was collected and a through ocular examination was performed. The data was collected in MS Excel and presented as numbers and percentages in the form of tables and figures. Results: Boys accounted for 54.8% of the participants and the rest 45.2% were girls. 40.8% subjects belonged to the age group 5-10 Years whereas 58.2 % belonged to the age group of 11-15 Years. The prevalence of Vitamin A deficiency in our study population was 5.2% which accounted to 13 children out of total 250. The prevalence of Vitamin A deficiency in our study population was 5.2% which accounted to 13 children out of total 250. Conclusion: There was low to moderate prevalence of Vitamin A Deficiency in our study population. Screening, Prophylactic therapy, Management of ocular diseases, Nutritional assessment and Health education are required.